Network Biology - Nookaew, Intawat; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book review series presents current trends in modern biotechnology. The aim is to cover all aspects of this interdisciplinary technology where knowledge, methods and expertise are required from chemistry, biochemistry, microbiology, genetics, chemical engineering and computer science. Volumes are organized topically and provide a comprehensive discussion of developments in the respective field over the past 3-5 years. The series also discusses new discoveries and applications. Special volumes are dedicated to selected topics which focus on new biotechnological products and new processes for their synthesis and purification. In general, special volumes are edited by well-known guest editors. The series editor and publisher will however always be pleased to receive suggestions and supplementary information. Manuscripts are accepted in English.
Network biology and modelling towards algal biofuel production -- Genome-scale metabolic network of thermophilic bacteria -- Network Approaches to Characterize Conformationa landscapes of Proteins: Applications to Drug Discovery -- Protein-protein Interface and Disease: Perspective from Biomolecular Network -- Rigid-docking approaches to Explore protein-protein interaction space -- Molecular phylogenetics: concepts and applications for Evolutionary network analysis -- ChIP-Seq data analysis to define regulatory networks -- Networking the omic data and Envisage the systems biological regulation -- Network Meta‐modeling: The Effect of Correlation Metric Choice on Phylogenomic and Transcriptomic Network Topology -- Network-guided novel key gene discovery -- Bioinformatics approaches for differential network analyses.
Keywords: Biotechnology; Proteins; Medicinal chemistry; Bioinformatics; Biotechnology; Proteins; Medicinal Chemistry; Bioinformatics